Tidal power : harnessing energy from water currents - q (Hoboken, New Jersey : Scrivener Publishing / Wiley, 2014)
As the global supply of conventional energy sources, such as fossil fuels, dwindles and becomes more and more expensive, unconventional and renewable sources of energy, such as power generation from water sources, is becoming more and more important. Hydropower has been around for decades, but this book suggests new methods that are more cost-effective and less intrusive to the environment for creating power sources from rivers, the tides, and other sources of water. The energy available from water currents is potentially much greater than society's needs. Presenting a detai.
Marine hydro kinetic- MHK 1 -- Rivers (channels) power plants without a dam -- Low-speed hydro-kinetic turbines -- Large power hydro turbines -- Examples of turbines produced -- Water current power-looking to the future.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Tidal power; Tidal power-plants.; Hydraulic turbines; Tide-waters.; Hydraulic turbines; Tidal power; Tidal power-plants.; TECHNOLOGY & ENGINEERING / Mechanical; Electronic books